(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article, on the example of Gafur Ghulam’s work "Shum bola", which is considered one of the masterpieces of Uzbek literature, the national spiritual spirit and nature of the images in children’s fiction, the interpretation of national thinking is expressed, and the character traits of the artistic images in the work are analyzed. and the aspects that reflect the national spirit are discussed.